2023
DOI: 10.1136/bmjopen-2023-072459
|View full text |Cite
|
Sign up to set email alerts
|

Unequal access? Use of sickness absence benefits by precariously employed workers with common mental disorders: a register-based cohort study in Sweden

Abstract: ObjectiveThis study compares the use of sickness absence benefits (SABs) due to a common mental disorder (CMD) between precariously employed and non-precariously employed workers with CMDs.DesignRegister-based cohort study.ParticipantsThe study included 78 215 Swedish workers aged 27–61 who experienced CMDs in 2017, indicated by a new treatment with selective serotonin reuptake inhibitors (SSRIs). Excluded were those who emigrated or immigrated, were self-employed, had an annual employment-based income <100… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 40 publications
0
0
0
Order By: Relevance
“…This could either be due to the work environment itself or to greater access to social benefits such as sickness absence among those in active jobs. In fact, a recent publication using a similar population found that those with lower quality employment were less likely to use sickness absence benefits, attributing this finding to presenteeism [31]. However, given that LTSA was generally lower among those in active jobs across levels of depression status, these explanations seem less likely.…”
Section: Interpretations Of the Resultsmentioning
confidence: 96%
“…This could either be due to the work environment itself or to greater access to social benefits such as sickness absence among those in active jobs. In fact, a recent publication using a similar population found that those with lower quality employment were less likely to use sickness absence benefits, attributing this finding to presenteeism [31]. However, given that LTSA was generally lower among those in active jobs across levels of depression status, these explanations seem less likely.…”
Section: Interpretations Of the Resultsmentioning
confidence: 96%